2021
DOI: 10.1021/acs.est.0c04849
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Fertilization History Alters Effects of Microplastics on Soil Properties, Microbial Communities, and Functions in Diverse Farmland Ecosystem

Abstract: Microplastics (MPs) pollution has caused a threat to soil ecosystem diversity and functioning globally. Recently, an increasing number of studies have reported effects of MPs on soil ecosystems. However, these studies mainly focused on soil bacterial communities and a few limited functional genes, which is why MPs effects on soil ecosystems are still not fully understood. Fertilization treatment often coinsides with MPs exposure in practice. Here, we studied effects of an environmentally relevant concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(48 citation statements)
references
References 70 publications
1
47
0
Order By: Relevance
“…Following the application of microplastics, the number of keystones in the networks decreased. The disappearance of keystone species may cause dissociation of module and network, indicating their important roles in maintaining network stability (Li et al ., 2021; Lu et al ., 2013). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the application of microplastics, the number of keystones in the networks decreased. The disappearance of keystone species may cause dissociation of module and network, indicating their important roles in maintaining network stability (Li et al ., 2021; Lu et al ., 2013). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al . (2021) conducted a short‐term microcosm experiment with polyethylene (PE) microplastics and three type soils (red soil, paddy soil, and fluvo‐aquic soil) and observed that microplastics reduced the pH of acid soil but increased the pH of alkaline soil. Yu et al .…”
Section: Introductionmentioning
confidence: 99%
“…The changes in soil exchangeable cations are shown in Table 2. MPs can provide reactive surfaces to exchange cations, which can vary depending on the MP type (Li et al, 2021). MP addition resulted in a significant increase in the exchangeable K + content under both moisture conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Fibers, microbeads, polyamides were majorly detected in a study conducted in vegetable farms [12]. Soils with different characteristics and type accompanied with higher exposure time to inorganic fertilizers collectively determine the effect of MPs on the soil [13]. Different types of soil and cropping patterns affect the role of MPs in changing pH or microbiota of the soil.…”
Section: Plastic Mulching As An Evident Microplastic Sourcementioning
confidence: 99%
“…Soil MPs have major effect on the soil pH accompanied by increment in plant and human pathogens in the soil [13]. MPs profoundly deteriorate the soil heath gradually.…”
Section: Potential Effects On Soil Texture and Propertiesmentioning
confidence: 99%